2017
DOI: 10.1016/j.psychres.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Examining FKBP5 mRNA expression in human iPSC-derived neural cells

Abstract: In peripheral blood leukocytes, FKBP5 mRNA expression is upregulated following glucocorticoid receptor activation. The single nucleotide polymorphism rs1360780 in FKBP5 is associated with psychiatric illness and has functional molecular effects. However, examination of FKBP5 regulation has largely been limited to peripheral cells, which may not reflect regulation in neural cells. We used 27 human induced pluripotent stem cell lines (iPSCs) derived from 20 subjects to examine FKBP5 mRNA expression following GR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…Following 12 weeks of neural maturation, iPSC-derived cultures contained dense Beta III-tubulin positive neurites ( Figure 1G), MAP2-positive neurons with pyramidal morphology (Figure 1H-I), and GFAP-positive astrocytes (Figure 1I). These findings are consistent with our prior work demonstrating this protocol efficiently generates mixed neural cell cultures with ~50% TBR1positive glutamate neurons that have the ability to generate trains of action potentials, display spontaneous synaptic activity indicative of synapse formation, and express functional glutamatergic and GABAergic ionotropic receptors, with no difference in the ability of iPSCs from control or AUD donors to generate neural cultures 24,25 .…”
Section: Ipscs Differentiate Into Frontal Cortical-like Neural Culturessupporting
confidence: 91%
See 2 more Smart Citations
“…Following 12 weeks of neural maturation, iPSC-derived cultures contained dense Beta III-tubulin positive neurites ( Figure 1G), MAP2-positive neurons with pyramidal morphology (Figure 1H-I), and GFAP-positive astrocytes (Figure 1I). These findings are consistent with our prior work demonstrating this protocol efficiently generates mixed neural cell cultures with ~50% TBR1positive glutamate neurons that have the ability to generate trains of action potentials, display spontaneous synaptic activity indicative of synapse formation, and express functional glutamatergic and GABAergic ionotropic receptors, with no difference in the ability of iPSCs from control or AUD donors to generate neural cultures 24,25 .…”
Section: Ipscs Differentiate Into Frontal Cortical-like Neural Culturessupporting
confidence: 91%
“…Following differentiation and plating onto matrigel-coated glass coverslips, neural cells were cultured and matured for 12 weeks prior to experimentation. Our prior work has demonstrated that 8-12 weeks of growth under this protocol generates neural cultures with functional electrophysiological properties as evidenced by mature action potentials, spontaneous synaptic activity, and expression of ligand-gated ionotropic receptors 24,25 . Neural cell markers were examined in differentiated iPSC lines 12 weeks after plating via immunostaining, as we have described.…”
Section: Neural Differentiation and Immunocytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In the human population, there is a wide variation in perception of stressful challenges, and variation in physiological expression of stress. Single nucleotide polymorphisms (SNPs) within the FKBP5 gene locus have been reported to impact stress responsivity, and risk or resilience to psychiatric disorders (Appel et al., 2011; Binder, 2009; Criado‐Marrero et al., 2019; Liebermann et al., 2017; Wilker et al., 2014). Differential expression levels of FKBP5 have preclinically been shown to impact on stress‐coping behavior and the SNP rs1360780 was reported to profoundly influence stress coping, suggesting FKBP5 genotypes as one source of human variation (Ising et al., 2008; Touma et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A series of papers has focused on iPSC-derived neurons in relation to alcohol dependence, FKBP5 regulation, and glucocorticoid activation ( 95 97 ). These cells express voltage-gated inward and outward currents, fire APs in response to current injection, respond to puff application of glutamate and GABA, and display spontaneous synaptic activity.…”
Section: Electrophysiological Analysis Of Ipsc-derived Neuronsmentioning
confidence: 99%